Pengaruh pH dan Konsentrasi pada Penyerapan Ion Logam Cu(II) Menggunakan Kulit Buah Matoa ( Pometia pinnata ) - Berliana Salsabila; Edi Nasra; Hardeli Hardeli; Indang Dewata; Desy Kurniawati (Periodic, 2023)
Â One of the effective methods in handling the impact of pollution by copper metal is the biosorption method using matoa peel powder (Pometia pinnata). The purpose of this research is to determine the optimum absorption conditions and the optimum capacity for absorption of copper metal ions (Cu2+) using the batch method with variations in pH, concentration, particle size, contact time, and stirring speed.. The results of the research showed that the optimum conditions for the absorption of Cu2+ metal ions were at pH 5, concentration of 220 ppm, particle size of 180 m, contact time of 90 minutes and stirring speed of 300 rpm was 12,059 mg/g. The adsorption isotherm of Cu2+ metal with matoa skin biosorbent (Pometia pinnata) tends to follow the Freundlich isotherm equation with a determinant coefficient (R) of 0,9992.Keywords â€” Biosorption, Metal ion Cu2+, pomettia pinnata, Batch method